Tingkat Risiko Pembiayaan Bermasalah dalam Akad Murabahah bil Wakalah Terhadap Eksistensi di Bank Syariah Indonesia - Desi Ayu Anita; Makhrus Makhrus (UM Purwokerto Press, 2022)
This study aims to find out what are the risks that arise due to non-performing financing and how to handle risks and maintain the existence of the bank. This research uses a type of field research with interview, observation and documentation data collection techniques. By using primary data sources derived from interviews and secondary data taken from journals, books, and legal products. Data analysis used an inductive method, namely establishing validity by studying related cases to draw conclusions. Based on research conducted by researchers, it can be concluded that non-performing financing is very risky to the asset quality of Islamic banks because of the Not Performing Financing, another risk experienced by banks, namely Indonesian Islamic banks experiencing a lack of capital ratios. Financing risk also occurs to customers. The risk that occurs to customers is that the customer will be included in the BI checking and SLIK black list. Therefore, in an effort to overcome non-performing financing, Bank Syariah Indonesia carried out several treatments and also prevention, namely an intensive approach with customers, maintenance, and deliberation.